Analisis Kebutuhan Gambar Interaktif PELITA Pada Platform Genially Materi Tata Surya Mata Pelajaran IPA Kelas V SD/MI - Sari, Ratna; Ibda, Hamidulloh (Tarbi: Jurnal Ilmiah Mahasiswa, 2025)
The lack of development of interactive image learning media on the Genial platform in science learning, especially solar system material in elementary/MI. The aim of this research is to identify the needs of students and teachers in developing interactive image learning media for solar system teaching materials in elementari/MI. The method used is quantitative through a survey with a cross sectional survey type according to Creswell. Research findings on the aspect of teacher needs for training in making interactive lamp images showed that the category score required 6 teachers (85.7%) and did not require 1 teacher (14.3%). The results of the analysis of student and teacher needs recommend the development of interactive lamp images on the Genially platform for material on the solar system for class V in elementary/MI science subjects because students need to get the highest 15 scores and teachers need to get the highest 14 scores from the 15 existing aspects.